PATRON CLIENT RELATIONS IN PANGLONG ARANG BUSINESS IN TELUK RHU VILLAGE, NORTH RUPAT DISTRICT - laila nurmasitoh; Rina Susanti (Jurnal Scientia, 2023)
This study aims to see the client patron relationship that exists between Javanese Medan charcoal panglong business actors in and tauke. This research was conducted using qualitative research methods with data collection techniques in the form of in-depth interviews, observations and documentation. The subjects of this study selected with a total of 4 main informants, namely Javanese Medan charcoal panglong business actors and 2 key informants, namely tauke who established relationships with charcoal panglong business actors in Teluk Rhu Village. The data analysis technique in this study uses the Miles and Huberman interactive analysis model scheme through three basic components in the form of data reduction, data presentation and conclusions. The results showed that the client's patron relationship in the charcoal panglong business actors and tauke provided benefits for both parties. The established client patron relationship breaks the stigma that the client patron relationship only benefits one party and exploits the other. Tauke as a patron provides benefits in relation by providing business capital, assistance, accounts receivable to business protection. Charcoal panglong business actors give their loyalty by only selling their production to one tauke as a reward for the assistance provided by tauke. The factors behind the establishment of patron client relations between charcoal panglong business actors and tauke are ethnic similarities (ethnicity), kinship (brotherhood), cooperation and comparison of the selling and buying prices of charcoal produced.